Rekitsen-RD bioactive food additive administered on regular basis: effects on runners' functionality rates - Sentyabrev, N. N.; Kamchatnikov, A. G.; Gorbaneva, E. P.; Solopov, I. N.; Juraev, A. R.; Koreneva, N. A. (Theory and Practice of Physical Culture, 2017)
Subject to the study were two groups of sprinters and middle-distance runners (Group 1 and 2), with the G1 athletes who have been administering the Rekitsen-RD bioactive food additive (BAFA) for one month and G2 being a reference group. At every stage of the study, the heart rate variability (HRV) of the subjects was tested. After the monthly experiment, tests showed a notable growth of the parasympathetic effects as verified by the HRV indices of G2 group versus the G1 test data showing an insignificant growth of sympathetic activity and ? growing trend of the role of the central regulatory system. In addition, the G1 athletes were tested with more expressed drop in tension of the regulation mechanisms. The regulatory system activity profiles for G2 showed the body adaptive capability falling trend versus the growing trend in G1. The above intergroup trends were supported by the significant intergroup differences of the HRV data. Having analyzed the training logs of the G1 athletes, we found subjectively rated improvements in the digestive and immune system conditions verified, among other things, by a drop in the infectious/cold sickness rates. There are reasons to believe that the positive effects of Rekitsen-RD BAFA are due to the immune and autonomous nervous system activities being consolidated and the regulatory system activity being improved with the balance insignificantly shifted towards the sympathetic activation mechanism.